How to be disobedient? Book review: Frédéric Gros: Nieposłuszeństwo. Transl. by E. Kaniowska. Wydawnictwo „Czarna Owca”. Warsaw 2019 - Krzyżowski, Adam (Folia Philosophica, 2021)
The review of the book is intended to highlight the main aporias raised by the French philosopher. It is based on the assumption that reading Frédéric Gros' work is a valuable source of information for anyone wishing to deepen their knowledge of both current and past social problems. The philosopher leads extraordinary research on the human individual who participates in the civic structure. The main element of the researcher's contemplation is the title disobedience, which is investigated through the prism of philosophy, science, history and even art. The author stands up for humanism and reason.